Pendampingan Perencanaan Gedung SDIT Darunnur Dengan Pendekatan Arsitektur Kontekstual - Al Husaini, Muhd Arief; Mashuri, Mashuri; Rijal, Muhammad; Hidayat, Wahyu; Suryani, R. Lisa; Susilawaty, Mira Dharma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Pematang Kapau is one of the villages in the Kulim District of Pekanbaru City, which experienced rapid population growth and urban development as a result of the Pekanbaru City Government's policy of moving the Pekanbaru City Government Center to Kulim District. Rapid development without being supported by adequate infrastructure will have a negative impact on urban areas. One of the things needed is educational facilities. Therefore, this activity helps the community, especially the Darunnur foundation in planning and designing educational facilities through Darunnur Mosque Foundation’s Integrated Islamic Elementary School Building Planning Assistance Program with a Contextual Architectural Approach. Contextual Architecture is a planning and design approach that considers the environment, culture, community character, history, so that the designed building has the characteristics of the form, as well as the quality of the building and the environment. The method used is descriptive qualitative, where the researcher is placed as the key instrument by combining field data with inductive analysis. This activity uses observation, discussion and design analysis methods. The results of this activity obtained the design of the Darunnur Mosque Foundation's Integrated Islamic Elementary School Building with a Contextual Architectural Approach.